Efficacy and Safety of Radiofrequency Ablation vs. Endoscopic Surveillance for Barrett’s Esophagus With Low-Grade Dysplasia: Meta-Analysis of Randomized Controlled Trials - Wang, Yizi; Ma, Bin; Yang, Shize; Li, Wenya; Li, Peiwen (Frontiers in Oncology, 2022)
Background and aims: Barrett’s esophagus with low-grade dysplasia (BE-LGD) carries a risk of progression to Barrett’s esophagus with high-grade dysplasia (BE-HGD) and esophageal adenocarcinoma (EAC). Radiofrequency ablation (RFA) appears to be a safe and efficacious method to eradicate Barrett’s esophagus. However, a confirmed consensus regarding treatment of BE-LGD with RFA vs. endoscopic surveillance is lacking. Therefore, this study aimed to elucidate the efficacy and safety for RFA vs. endoscopic surveillance in decreasing the risk of BE-LGD progression to BE-HGD or EAC. Methods: Relevant studies published before May 1, 2021 were identified by searching relevant medical databases. The primary outcome was the rate of progression BE-LGD to HGD and/or EAC after treatment with RFA and endoscopic surveillance. The secondary outcome was the rate of complete eradication of dysplasia (CE-D) and complete eradication of intestinal metaplasia (CE-IM) after treatment with RFA and endoscopic surveillance. Adverse events were also extracted and evaluated. Results: Three randomized controlled trials were eligible for analysis. The pooled estimate of rate of neoplastic progression of BE-LGD to HGD or EAC was much lower in the RFA group than the endoscopic surveillance group (RR, 0.25; 95% CI, 0.07–0.93; P = 0.04), with moderate heterogeneity (I2 = 55%). Subgroup analysis based on progression grade was performed. The pooled rate of progression of BE-LGD to HGD was much lower in the RFA group than the endoscopic surveillance group (RR, 0.25; 95% CI, 0.07–0.71; P = 0.01), with low heterogeneity (I2 = 15%). Although the pooled risk of progression of BE-LGD to EAC was slightly lower in the RFA group than the endoscopic surveillance group (RR, 0.56; 95% CI, 0.05–6.76), the result was not statistically significant (P = 0.65). RFA also was associated a higher rate of CE-D and CE-IM both at the end of endoscopic treatment and during follow-up. However, the rate of adverse events was slightly higher after RFA treatment. Conclusion: RFA decreases the risk of BE-LGD progression to BE-HGD. However, given the uncertain course of LGD and the potential for esophageal stricture after RFA, treatment options should be fully considered and weighed.